Intestinal injury caused by Eimeria spp. impairs the phosphotransfer network and gain weight in experimentally infected chicken chicks - Galli G.M.* (2019)
© 2019, Springer-Verlag GmbH Germany, part of Springer Nature.Parasitic infections caused by protozoan belonging to genus Eimeria are considered important for the poultry industry, due to their severe intestinal lesions and high mortality rates, causing significant economic losses. Although several mechanisms of coccidiosis pathogenesis are known, the effects of this infection on intestinal enzymes linked to adenosine triphosphate (ATP) metabolism, as creatine kinase (CK), adenylate kinase (AK), and pyruvate kinase (PK), remain unknown. Thus, the aim of this study was to evaluate whether coccidiosis impairs enzymes linked ATP metabolism in the intestine of chicken chicks. For this, 42 animals that were 2 days old were divided into two groups: uninfected (the negative control group) and experimentally infected on second day of life (the positive control group). On days 5, 10, and 15 post-infection (PI), fecal samples were collected for oocyst counts; intestinal tissue was collected in order to evaluate CK, AK, and PK activities, as well as parameters of the oxidative stress and histopathology. On days 10 and 15 PI, infected animals showed high counts of oocysts in fecal samples and intestinal lesions compared to the control group. Cytosolic CK activity was higher in infected animals on days 10 and 15 PI compared to the control group, while mitochondrial CK activity was lower on days 5, 10, and 15 PI. Also, AK activity was lower in infected animals on days 10 and 15 PI compared to control group, while no differences were observed between groups regarding PK activity. In relation to parameters of oxidative stress, intestinal lipid peroxidation and reactive oxygen species levels were higher in infected animals on days 10 and 15 PI compared to the control group, while non-protein thiol levels were lower on day 10 PI. On the 15th day, infected animals had lower body weight (P < 0.05). Based on this evidence, inhibition of mitochondrial CK activity causes an impairment of intestinal energetic homeostasis possibly through depletion on ATP levels, although the cytosolic CK activity acted as an attempt to restore the mitochondrial ATP levels through a feedback mechanism. Moreover, the impairment on energy metabolism appears to be mediated by excessive production of intestinal ROS, as well as oxidation of lipids and thiol groups.